Fishery and production of shrimps from perennial and seasonal fields of Kerala - Pillai, S M (Indian Journal of Fisheries, 2011)
The fishery and production of shrimps from a perennial field and seasonal filtration field of Vypeen Island, Cochin is reported. Penaeus indicus, P.monodon, Metapenaeus dobsoni and M.monoceros constituted the shrimp fishery in both the fields. Very rarely P.semisulcatus and M.affinis were noticed in the catches. Compared to the seasonal field, large sized shrimps were found in the perennial field. Only M.dobsoni showed significant size difference between seasonal and perennial fields (P< 0.001). The catch was largely contributed by P.indicus in both perennial (65.0%) and seasonal (55.4 %) fields and followed by M.dobsoni, M.monoceros and P.monodon. In 12 months, the total shrimp catch from the perennial field was 4021.77 kg and the production, 209.47 kg/ha. However, from the seasonal field total catch of 1662.70 kg was obtained in 4 months and the production was 353.77 kg/ha. Comparison of the catch data of shrimps from the perennial field to the corresponding period of operation of seasonal field (December- March) revealed that the total catch from perennial field was only 789.70 kg and the production was as low as 41.13 kg/ha. In both the fields, P.indicus dominated the catches in February.